Spatial impact of urban expansion on lake surface water temperature based on the perspective of watershed scale - Tang, Linfeng; Yang, Kun; Shang, Chunxue; Peng, Zongqi; Luo, Yi (Frontiers in Environmental Science, 2022)
As an important ecological environmental factor, the lake water surface temperature (LSWT) has an important impact on the ecological diversity of lakes and watersheds. With the acceleration of urbanization in China, the impact of urban expansion on LSWT can not be ignored. In this study, the spatial influence（G）equation was introduced to quantify the impact of IS expansion on LSWT. MOD11A2 was used as the data source (R2 = 0.87, RMSE = 1.82 °C), and six lakes with fast urban expansion in China are taken as the study area to carry out demonstration research. The results show that (1) The IS in the six watersheds all experienced significant expansion, with an increase of 1.80-3.91 times. （2）From the annual average LSWT from 2001 to 2018, only Poyang Lake's LSWT-night shows a cooling trend, while other lakes, whether LSWT-day or LSWT-night, show a warming trend. (3) G is used to comprehensively consider the area change of IS in the watershed, the influence of distance and the change of lake area, which can quantify the impact of IS on LSWT, so as to further explain and describe the spatial influence process and characteristics of IS expansion on LSWT.